Improve rail services to become choices mode - Azmi, Siti Sarwani; Zainuddin, Nizamuddin (2012)
This study is an overview of the consumer perception towards rail transportation services.In Malaysia, the public transportation system is an important aspect of communications system either for the urban community or rural areas.This study will try to find out what aspects might cause rail transportation services become last choice during festive seasons, while demand for bas cannot be fulfill.100 sample to examine the main cause why this might happen.Many problem can overcome when consumer choose rail transport as their mode to travel, example like traffic congestions, accidents, fuel demand and air pollutions.